ROLE OF EMOTIONS IN THE CONSTRUCTION OF DISCOURSE ACCORDING TO THE SEMIOLOGICAL THEORY OF PATRICK CHARAUDEAU (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article presents an in-depth analysis of the role of emotions in the construction of discourse, through the semiological theory of Patrick Charaudeau. He explores how emotions are not simply spontaneous reactions, but strategic tools that influence the way messages are perceived and interpreted by receivers. The author highlights the link between emotions and meaning, and shows how emotions are integrated into various types of discourse to guide individuals' actions, beliefs and behaviors.